Method for preparing manganese-based catalyst through 3D printing, prepared catalyst and application
The preparation of ceramic carriers with a connecting channel structure and coating a slurry containing manganese oxide on the surface is solved by 3D printing, which solves the problems of limited loading of manganese-based catalysts and limited catalytic oxidation activity, and achieves efficient VOCs treatment and cost reduction.
Patent Information
- Application Number
- CN202311001601.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-09
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2043-08-09
AI Technical Summary
The existing manganese-based catalysts have limited loading on conventional supports, and the catalytic oxidation activity is limited. The specific surface area of the support material obtained by 3D printing is reduced during the sintering process, which is not conducive to improving the loading and activity of the catalyst.
The ceramic support with a connecting channel structure was prepared by 3D printing, and the surface of which was coated with a slurry containing manganese oxide was expanded, and the specific surface area of the support was increased by alkali treatment, thereby increasing the loading of the manganese-based active components and catalytic oxidation activity.
The catalytic oxidation activity of the catalyst is improved, the diffusion and contact conditions of reactants are improved, the treatment efficiency of VOCs is enhanced, and the cost of the catalyst is reduced.
Smart Images

Figure CN119500106A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of 3D printing and catalytic materials, and in particular to a method for preparing a manganese-based catalyst by 3D printing, and the prepared catalyst and its application. Background Art
[0002] PM 2.5 The control of O3 pollution is still a huge challenge in solving the problem of regional atmospheric complex pollution in my country. Volatile organic compounds (VOCs) are organic compounds with a saturated vapor pressure higher than 133.32 Pa and a boiling point between 50-250°C. VOCs have become the second largest x The key factor that restricts further improvement of air quality is that emission control is imminent.
[0003] In the control of VOCs emissions from industrial sources, catalytic oxidation is one of the most promising methods. Compared with traditional adsorption and absorption methods, secondary pollution is significantly reduced. The catalytic oxidation method can significantly reduce the oxidation temperature of VOCs, reduce the generation of by-products, and reduce energy consumption. The development of high-performance, low-cost, and long-life VOCs oxidation catalysts is the key to this technology. At present, industrial source VOCs oxidation catalysts mostly use honeycomb carrier integral catalytic materials, usually using inert materials such as honeycomb cordierite and honeycomb ceramics as carriers, coupled with rare earth or transition metal oxide coatings, and using precious metals such as Pt and Pd as the main active components. CN106890642B discloses a catalyst for treating benzene substances in industrial waste gas and a preparation method thereof. The ignition temperature of the VOCs oxidation reaction is reduced by coating the active components twice on the honeycomb ceramic carrier. Although the above invention can improve the performance of the catalyst under the test conditions, the honeycomb cordierite or ceramic carrier is a one-dimensional array channel structure. In actual working conditions, due to problems such as uneven flue gas distribution and insufficient flue gas residence time, there are defects such as insufficient VOCs treatment efficiency at high air velocity or the need to increase the catalyst filling amount. Therefore, improving the traditional one-dimensional array honeycomb channel structure is the key to solving this problem, which can improve the uniformity of flue gas distribution and increase the flue gas residence time, reduce costs and improve efficiency.
[0004] 3D printing technology is a new type of intelligent manufacturing technology that uses computer-controlled material stacking to form a three-dimensional target structure. Compared with traditional material processing technology, 3D printing is not limited to molds, and has the characteristics of high raw material utilization, strong structural design, and high structural adjustment flexibility. It is an ideal method for designing three-dimensional cross-linked channel carrier materials. Hajimirzaee et al. used computational fluid dynamics analysis to confirm that 3D printed carriers significantly improve the turbulence of airflow, turbulence / mass transfer and surface area (Fuel, 2020, 274: 117848), indicating that 3D printed carriers have outstanding application potential in the field of VOCs catalytic oxidation. However, the carrier materials obtained by 3D printing often need to be sintered at high temperature to improve their high mechanical strength, thereby increasing the service life of the relevant regular catalytic materials. The sintering process usually reduces the specific surface area of the carrier material, which is not conducive to increasing the catalyst loading. This defect still needs to be overcome.
[0005] On the other hand, mature commercial precious metal catalysts have been restricted from further promotion and use in the industry due to their high cost, and the development of high-performance, low-cost alternative materials has become an urgent need. Manganese-based catalysts have received extensive attention from academia and industry due to their economy and excellent redox properties. They have VOCs oxidation performance comparable to or even better than precious metal catalysts, reflecting broad application prospects (Chemical Review, 2019, 119 (7): 4471-4568). However, there is still a problem that the loading amount of manganese-based active components on the carrier is limited and the catalytic oxidation activity is limited. Therefore, a catalyst preparation method that can effectively increase the loading amount of manganese-based active components on the catalyst and improve the catalytic oxidation activity of the catalyst is needed. Summary of the invention
[0006] The purpose of the present invention is to overcome the problems in the prior art that the loading amount of manganese-based active components on conventional carriers is limited, the pore structure of the prepared catalyst carrier is single, which is not conducive to the diffusion of reactants in the catalytic oxidation process, and the contact between the reactants and the active components is limited, thereby affecting the catalytic oxidation activity of the catalyst. A method for preparing a manganese-based catalyst by 3D printing and the prepared catalyst and application are provided. The method realizes the preparation of a manganese-based catalyst by coating, and loads a manganese oxide with strong redox properties onto a carrier with a connected pore structure. The coating method is simple to operate, and the catalytic oxidation activity of the catalyst is improved by combining the manganese-based active component with the carrier during the preparation process.
[0007] In order to achieve the above object, the first aspect of the present invention provides a method for preparing a manganese-based catalyst by 3D printing, which comprises the following steps:
[0008] (1) mixing a photosensitive resin mixed liquid with a ceramic powder to obtain a photosensitive ceramic slurry, and performing 3D printing to obtain a printed body;
[0009] (2) degreasing and sintering the printed body to obtain a 3D printed ceramic carrier;
[0010] (3) Coating a slurry containing manganese oxide on the surface of a 3D printed ceramic carrier and calcining the slurry to obtain a manganese-based catalyst.
[0011] Preferably, in step (2), the degreasing of the printed body is divided into two stages: in the first stage, the temperature is increased to 450-550°C at a rate of 3-8°C / min and maintained for 0.5-4h, preferably, the temperature is increased to 460-530°C at a rate of 3-7°C / min and maintained for 1-3h;
[0012] In the second stage, the temperature is further increased to 650-750°C at a rate of 8-15°C / min and maintained for 1-3h, preferably increased to 680-720°C at a rate of 8-12°C / min and maintained for 2-3h.
[0013] Preferably, step (3) further comprises alkali treatment of the 3D printed ceramic carrier before coating, and the alkali treatment process comprises: immersing the 3D printed ceramic carrier in alkali solution at 30-80° C. for 0.5-10 h, preferably 1-6 h.
[0014] Preferably, in step (3), the total coating amount of the slurry containing manganese oxide per liter of the 3D printing ceramic carrier is 40-160 g, preferably 50-130 g.
[0015] The second aspect of the present invention provides a manganese-based catalyst prepared by the method described in the first aspect.
[0016] Preferably, the manganese-based catalyst comprises a support and a manganese oxide coated on the surface of the support.
[0017] Preferably, the specific surface area of the carrier of the manganese-based catalyst is 6-20 m 2 / g, preferably 8-15m 2 / g.
[0018] Preferably, the specific surface area of the manganese oxide coated on the surface of the manganese-based catalyst is 10-80 m 2 / g, preferably 20-60m 2 / g.
[0019] The third aspect of the present invention provides a use of the manganese-based catalyst described in the second aspect in a catalytic oxidation reaction.
[0020] Through the above technical solution, the beneficial effects obtained are as follows:
[0021] (1) In the present invention, a ceramic carrier is prepared by 3D printing to obtain a carrier having three-dimensional interconnected pores and a vertically staggered structure, and a slurry containing manganese oxide is coated on the surface of the carrier. Since manganese oxide has strong redox properties, the utilization efficiency of the catalytically active components of the prepared catalyst can be improved, thereby improving the catalytic oxidation activity of the catalyst;
[0022] (2) In the present invention, preferably, the ceramic carrier prepared by 3D printing has a rich pore structure, which can fully expose the catalytic active components, effectively alleviate the problems of uneven airflow distribution and insufficient residence time of the reactants in the catalyst pores, improve the reaction contact conditions, and have a higher conversion rate when performing VOCs catalytic oxidation reactions;
[0023] (3) In the present invention, preferably, the preparation of the integral manganese-based catalyst is achieved by coating on a 3D printed ceramic carrier, which is easy to operate, the manganese-based active components are uniformly loaded on the carrier surface, and manganese oxide is used to replace precious metals, thereby reducing the cost of the catalyst. It is suitable for mass production and is expected to be extended to the preparation of various fixed-bed catalytic materials, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a schematic diagram of the 3D printing model structure of Example 1;
[0025] Figure 2 This is a physical photo of the manganese-based catalyst of Example 1;
[0026] Figure 3 It is a relationship diagram of the conversion rate of catalytic oxidation of propane-temperature for Examples 1-6 and Comparative Examples 1-4. DETAILED DESCRIPTION
[0027] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0028] A first aspect of the present invention provides a method for preparing a manganese-based catalyst by 3D printing, which comprises the following steps:
[0029] (1) mixing a photosensitive resin mixed liquid with a ceramic powder to obtain a photosensitive ceramic slurry, and performing 3D printing to obtain a printed body;
[0030] (2) degreasing and sintering the printed body to obtain a 3D printed ceramic carrier;
[0031] (3) Coating a slurry containing manganese oxide on the surface of a 3D printed ceramic carrier and calcining the slurry to obtain a manganese-based catalyst.
[0032] In the present invention, a 3D printed carrier is combined with a manganese-based active component, a slurry containing manganese oxide is coated on the surface of the 3D printed ceramic carrier, the manganese-based active component is uniformly loaded on the carrier surface, and a manganese-based catalyst is obtained after calcination and stabilization treatment. Since manganese oxide has strong redox properties, it can not only improve the one-dimensional array honeycomb pore structure limitations of traditional monolithic catalysts, but also effectively improve the reactant diffusion and contact limitations of the catalyst in the catalytic oxidation reaction, thereby improving the catalytic performance.
[0033] According to the present invention, preferably, based on 100 parts by mass of the photosensitive resin mixed liquid, it includes 0.5-10 parts of photoinitiator, 85-95 parts of photosensitive resin, and 2-10 parts of powder dispersant, and preferably includes 3-8 parts of photoinitiator, 88-92 parts of photosensitive resin, and 3-5 parts of powder dispersant.
[0034] In the present invention, the photosensitive resin mixed liquid is obtained by uniformly mixing a photoinitiator, a photosensitive resin and a powder dispersant. The mixing method is not particularly limited and those skilled in the art can adjust it as needed to obtain a uniformly mixed photosensitive resin mixed liquid.
[0035] According to the present invention, the photoinitiator can be a conventional photoinitiator in the art. Preferably, the photoinitiator is selected from at least one of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (photoinitiator TPO), phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide (photoinitiator 819) and isopropylthioxanthone (ITX).
[0036] According to the present invention, the specific composition of the photosensitive resin has a wide range of choices and can be selected according to conventional technical means in the art. Preferably, the photosensitive resin is a mixture of an acrylate prepolymer and an acrylate monomer, and the acrylate prepolymer is an epoxy acrylate prepolymer and / or a polyurethane acrylate prepolymer.
[0037] In the present invention, the acrylic ester monomer may be a conventional acrylic ester monomer in the art, and is preferably at least one selected from 1,6-hexanediol diacrylate (HDDA), tripropylene glycol diacrylate (TPGDA) and trimethylolpropane triacrylate (TMPTA).
[0038] In the present invention, the powder dispersant is a commonly used commercial dispersant, preferably at least one selected from sulfate ester powder dispersants, polyol powder dispersants, polyurethane powder dispersants and silane coupling agent powder dispersants.
[0039] According to the present invention, preferably, the mass ratio of the acrylate prepolymer to the acrylate monomer in the photosensitive resin is 1:0.6-2.2, for example, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1, 1:1.2, 1:1.4, 1:1.6, 1:1.8, 1:2, 1:2.2, and any range between any two values, preferably 1:0.8-2.
[0040] According to the present invention, preferably, in step (1), the mass ratio of the ceramic powder to the photosensitive resin mixture is 1:0.1-2, such as 1:0.1, 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.8, 1:1, 1:1.2, 1:1.4, 1:1.6, 1:1.8, 1:2, and any range between any two values, preferably 1:0.2-1.6. The photosensitive ceramic slurry obtained by mixing according to the above mass ratio has a fast curing speed when 3D printing is subsequently performed, and the structural stability of the carrier material obtained after sintering is better.
[0041] In the present invention, the mixing method of the photosensitive resin mixed liquid and the ceramic powder is not particularly limited, and the photosensitive resin mixed liquid and the ceramic powder are evenly mixed to obtain a photosensitive ceramic slurry. According to a preferred embodiment of the present invention, the photosensitive resin mixed liquid is placed in a high-speed disperser, and the ceramic powder is slowly poured in. During the process, the high-speed disperser is turned on for stirring, and the stirring rate is 400-650rpm / min. When the ceramic powder is completely poured in, continue stirring for 20-60min to obtain a preliminarily mixed photosensitive ceramic slurry. The above slurry is repeatedly ground in a ball mill for 3-5 times, each grinding time is 0.5-2h, and the rotation speed is 100-500rpm, and the photosensitive ceramic slurry is ground.
[0042] In the present invention, the type of the ball mill is not particularly limited, and can be a conventional ball mill in the art. Preferably, a planetary ball mill is used.
[0043] According to the present invention, preferably, the ceramic powder is a natural aluminosilicate mineral clay, preferably at least one selected from cordierite, kaolin and bentonite.
[0044] According to the present invention, there is no particular limitation on the average particle size of the ceramic powder. Preferably, the average particle size of the ceramic powder is less than 10 μm, preferably 2.5-5 μm. The use of ceramic powder with an average particle size less than 10 μm is more conducive to uniformly mixing the photosensitive resin mixture with the ceramic powder, obtaining a photosensitive ceramic slurry with better dispersion, fast curing speed during 3D printing, and high production efficiency. If the particles of the ceramic powder are large, it is preferred to further improve their uniformity through subsequent ball milling.
[0045] In the present invention, a printing body is prepared by 3D printing, a three-dimensional structure is designed using modeling software, a photosensitive ceramic slurry is placed in a 3D printer material cylinder, a three-dimensional model is introduced, and 3D printing is performed after computer slicing to obtain a printing body with a connected pore structure.
[0046] In the present invention, preferably, a modeling software is used for three-dimensional structure design, and the modeling software is selected from SolidWorks, 3DMAX, AutoCAD or Materialise Magics.
[0047] According to the present invention, preferably, the 3D printing conditions include: single layer curing thickness 20-150 μm, single layer illumination time 5-20 s, illumination intensity 2-10 mW / cm 2 .
[0048] In the present invention, the "printed blank" is a general term for the prepared blanks. The printing method can be used to customize complex three-dimensional structures suitable for different scenarios. It does not rely on molds and does not require complex post-processing of the carrier. Compared with traditional carrier processing methods, the interconnected channel structure of the carrier is simple and controllable, with good regularity, high raw material utilization, and the structure can be flexibly adjusted.
[0049] In the present invention, there is no particular limitation on the size and structure of the printed body, and those skilled in the art can make appropriate selections according to the specific application scenarios of the prepared catalyst. The present invention subsequently provides a specific preferred embodiment for use in a catalytic oxidation catalyst, but the present invention is not limited thereto.
[0050] The present invention does not specifically limit the interconnected pore structure, which has the conventional meaning in the art. In the present invention, the interconnected pore structure refers to the cross-connected pores in the vertical and horizontal directions of the printed body, which have good permeability. There is no specific limitation on the distribution of the pores, and those skilled in the art can make adaptive selections based on the specific catalyst preparation conditions. The distribution of the pores can be uniform, symmetrical, or uneven, asymmetrical. According to a preferred embodiment of the present invention, the specific pore structure is as follows Figure 1 and Figure 2 shown.
[0051] According to the present invention, preferably, the printed body has a vertically staggered structure composed of cubic columns with a bottom side length of 0.5-2 mm. The printed body with the above structure is used as a carrier to prepare a manganese-based catalyst after being treated, which can effectively alleviate the problem of uneven airflow distribution and insufficient residence time of the raw material in the catalyst pores, and improve the reaction contact conditions.
[0052] In the present invention, the vertical staggered structure has the conventional meaning in the art, and refers to a mutually perpendicular structure formed by overlapping cubic columns, such as Figure 1 As shown. A cubic column refers to a column formed by two equal bases of squares and sides perpendicular to the bases. The base length refers to the length of the side of the base of the cubic column.
[0053] According to the present invention, the degreasing process of the printed body is not particularly limited, and those skilled in the art can make adaptive adjustments according to the degreasing conditions of the printed body, as long as the organic matter in the body is removed so that the inorganic material is solidified into a ceramic material. Preferably, the degreasing process of the printed body includes: a heating temperature of 400-800°C and a heating time of 1-10h.
[0054] Further preferably, in step (2), the process of degreasing the printed body comprises:
[0055] In the first stage, the temperature is increased to 450-550°C at a rate of 3-8°C / min and maintained for 0.5-4h, preferably increased to 460-530°C at a rate of 3-7°C / min and maintained for 1-3h;
[0056] In the second stage, the temperature is further increased to 650-750°C at a rate of 8-15°C / min and maintained for 1-3h, preferably increased to 680-720°C at a rate of 8-12°C / min and maintained for 2-3h.
[0057] In the present invention, preferably, the degreasing is carried out in two stages. In the first stage, the heating temperature is controlled to be low and the heating rate is slow, so that the structure of the printed body can be kept intact while removing the organic matter in the printed body. The heating rate is controlled at 3-8°C / min to avoid excessive heating to cause cracks in the body. In the second stage, the heating temperature is increased to solidify the inorganic material in the printed body into porcelain.
[0058] According to the present invention, preferably, the sintering conditions include: sintering temperature of 1300-1600°C, preferably 1350-1500°C; sintering time of 1-3h, preferably 1.5-2.5h; heating rate of 8-15°C / min, preferably 9-12°C / min. In the present invention, sintering is carried out under the above sintering conditions to obtain a 3D printed ceramic carrier with high mechanical strength and large specific surface area, providing support for the subsequent coating of the slurry containing manganese oxide while loading more active components.
[0059] According to the present invention, preferably, after sintering, the temperature is cooled to room temperature at a cooling rate of 3-8°C / min, preferably 4-6°C / min.
[0060] According to the present invention, preferably, step (3) further comprises alkali treatment of the 3D printed ceramic carrier before coating, and the alkali treatment process comprises: immersing the 3D printed ceramic carrier in alkali solution at 30-80°C for 0.5-10h, preferably 1-6h.
[0061] In the present invention, alkali treatment helps to expand the specific surface area of the carrier to form a three-dimensional through-hole structure. A slurry containing manganese oxide is coated on the carrier after alkali treatment to prepare a manganese-based catalyst. The carrier with a three-dimensional through-hole structure is combined with a manganese-based active component, which can accelerate the diffusion of reactants in the catalytic oxidation reaction, and the catalytic oxidation reaction activity of the catalyst is significantly improved.
[0062] According to the present invention, preferably, the alkali solution is a NaOH and / or KOH aqueous solution, and the mass fraction of NaOH and / or KOH is 4%-20%, preferably 6-18%.
[0063] According to the present invention, preferably, the mass ratio of the 3D printing ceramic carrier: the alkali solution is 1:4-10, preferably 1:5-9.
[0064] According to the present invention, preferably, the specific surface area of the 3D printing ceramic carrier after alkali treatment is 6-20m 2 / g, preferably 8-15m 2 / g.
[0065] In the present invention, the specific surface area of the 3D printed ceramic carrier after alkali treatment is measured by low temperature nitrogen adsorption capacity method, and the test instrument is ASAP2400 static nitrogen adsorption instrument of Micromeritics. Test conditions: the sample is vacuum degassed at 1.33Pa and 300°C for 4h, and then contacted with liquid nitrogen at 77K, isothermally adsorbed and desorbed, and the adsorption and desorption isotherms are measured, and the specific surface area is calculated using the BET formula.
[0066] In the present invention, preferably, the steps of washing and drying the 3D printed ceramic carrier after alkali treatment are also included, and the conditions of washing and drying are not particularly limited, and those skilled in the art can make appropriate selections. According to a preferred embodiment of the present invention, the 3D printed ceramic carrier is rinsed with deionized water 3-5 times after alkali treatment and dried at 80-120°C.
[0067] In the present invention, the 3D printed ceramic carrier provides a skeleton for the catalyst, the printed body has a connected pore structure, and after degreasing and sintering, a 3D printed ceramic carrier is formed. A slurry containing manganese oxide is coated on the surface of the 3D printed ceramic carrier to obtain a manganese-based catalyst, thereby improving the catalytic oxidation activity of the catalyst.
[0068] According to the present invention, preferably, in step (3), the total coating amount of the slurry containing manganese oxide per liter of 3D printed ceramic carrier is 40-160g, such as 40g, 50g, 60g, 70g, 75g, 80g, 90g, 100g, 110g, 120g, 130g, 140g, 150g, 160g, and any range composed of any two values, preferably 50-130g. The use of this embodiment is more conducive to fully exposing the active component manganese oxide to the surface of the carrier and improving the utilization efficiency of the active component. If the coating amount is too small, the content of the active component is insufficient, and the catalytic oxidation activity of the catalyst is poor; if the coating amount is too large, the adhesion of the coating is reduced, and it is easy to fall off under the impact of airflow, or block the connecting pores of the carrier to cause uneven airflow distribution.
[0069] In the present invention, the volume of the 3D printed ceramic carrier is calculated according to the carrier dimensions obtained by 3D printing. In the present invention, the total coating amount of the slurry containing manganese oxide is calculated by the mass difference between the calcined catalyst and the original 3D printed ceramic carrier.
[0070] According to the present invention, preferably, the manganese oxide-containing slurry comprises manganese oxide powder and deionized water.
[0071] According to the present invention, preferably, the average diameter of the manganese oxide powder in the manganese oxide-containing slurry is less than 15 μm, preferably 7-13 μm.
[0072] In the present invention, preferably, the manganese oxide-containing slurry is obtained by uniformly mixing manganese oxide powder and deionized water, and the mixing method is not particularly limited, as long as a uniformly mixed manganese oxide-containing slurry is obtained. According to a preferred embodiment of the present invention, manganese oxide powder is added to deionized water, concentrated nitric acid is added to adjust the pH value of the system to less than 4, and the mixed solution is fully ground. The grinding conditions are not particularly limited, so that the manganese oxide powder and deionized water are uniformly mixed, and the average diameter of the manganese oxide powder in the obtained manganese oxide-containing slurry is less than 15 μm.
[0073] In the present invention, there is no particular limitation on the concentration and addition amount of the concentrated nitric acid, as long as the pH value of the system is less than 4.
[0074] In the present invention, preferably, the grinding is achieved by ball milling, and the ball milling conditions include: ball milling time 1-5h, rotation speed 500-1500rpm. The ball milling equipment is not particularly limited, and is preferably a vibrating ball mill.
[0075] According to the present invention, preferably, the mass ratio of the manganese oxide powder to deionized water is 1:2.5-9, for example 1:2.5, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, and any range between any two values, preferably 1:3-6.
[0076] According to the present invention, preferably, the manganese oxide powder is selected from at least one of single manganese oxides, manganese-based spinels, manganese-based perovskites, and manganese-based mullites.
[0077] According to the present invention, preferably, the single manganese oxide is selected from at least one of α-MnO2, β-MnO2, γ-MnO2, δ-MnO2, λ-MnO2, ε-MnO2, α-Mn2O3, and Mn3O4.
[0078] According to the present invention, preferably, the manganese-based spinel includes A x Mn 3-x O4, where A is selected from at least one of Mg, Ca, Fe, Co, Ni, Cu, and Zn, and 0 < x < 3.
[0079] According to the present invention, preferably, the manganese-based perovskite includes BMnO3, where B is selected from at least one of La, Sm, Sr, and Ca.
[0080] According to the present invention, preferably, the manganese-based mullite includes CMn2O5, where C is selected from at least one of Y, La, and Sm.
[0081] In the present invention, preferably, the manganese oxide powder is selected from at least one of α-MnO2, Cu x Mn 3-x O4, and Fe x Mn 3-x O4, where 0 < x < 3. In the present invention, the source of the manganese oxide powder is not particularly limited and can be commercially purchased or prepared by existing methods as long as it can be used to prepare the slurry containing manganese oxide.
[0082] In the present invention, preferably, it further includes a process of drying and then roasting the 3D printed ceramic carrier coated with the slurry containing manganese oxide. The drying conditions are not particularly limited, and those skilled in the art can make adaptive adjustments according to needs. Preferably, the drying temperature is 100 - 140°C.
[0083] According to the present invention, preferably, in step (3), the roasting temperature is 300 - 650°C, preferably 400 - 450°C, and the roasting time is 1 - 5 h, preferably 2 - 4 h.
[0084] According to the present invention, preferably, when the manganese oxide powder contains at least one of α-MnO2, β-MnO2, γ-MnO2, δ-MnO2, λ-MnO2, ε-MnO2, and manganese-based spinel, the roasting process includes: heating up to 300 - 450°C at a rate of 3 - 6°C / min and holding for 2 - 4 h.
[0085] According to the present invention, preferably, when the manganese oxide powder does not contain at least one of α-MnO2, β-MnO2, γ-MnO2, δ-MnO2, λ-MnO2, ε-MnO2 and manganese-based spinel, the calcination process includes: heating to 350-650°C at a rate of 3-6°C / min and maintaining for 2-4h.
[0086] In the present invention, preferably, different calcination temperatures are controlled to ensure that the manganese oxide does not undergo phase change during the calcination process. For example, when the manganese oxide powder contains at least one of α-MnO2, β-MnO2, γ-MnO2, δ-MnO2, λ-MnO2, ε-MnO2 and manganese-based spinel, if the calcination temperature exceeds 450°C, phase change is likely to occur and the active components are sintered. When the manganese oxide powder does not contain at least one of α-MnO2, β-MnO2, γ-MnO2, δ-MnO2, λ-MnO2, ε-MnO2 and manganese-based spinel, the manganese oxide can withstand calcination at 350-650°C without phase change.
[0087] The second aspect of the present invention provides a manganese catalyst prepared by the method described in the first aspect.
[0088] According to the present invention, preferably, the manganese-based catalyst comprises a carrier and a manganese oxide coated on the surface of the carrier. In the present invention, the surface of the carrier includes the inner surface and the outer surface of the carrier.
[0089] According to the present invention, preferably, the specific surface area of the carrier of the manganese-based catalyst is 6-20m 2 / g, preferably 8-15m 2 / g.
[0090] According to the present invention, preferably, the specific surface area of the manganese oxide coated on the surface of the manganese-based catalyst is 10-80m 2 / g, preferably 20-60m 2 / g.
[0091] In the present invention, preferably, the test method for the specific surface area of the manganese oxide coated on the surface of the manganese-based catalyst is the same as the test method for the specific surface area of the carrier, which is described in the aforementioned specification and will not be repeated here.
[0092] The third aspect of the present invention provides a use of the manganese-based catalyst described in the second aspect in a catalytic oxidation reaction.
[0093] According to the present invention, preferably, the manganese-based catalyst is used in the catalytic oxidation reaction of VOCs.
[0094] In the present invention, there is no particular limitation on the composition of the VOCs, which are conventional volatile organic compounds in the art, including at least one of alkanes (straight-chain alkanes and cycloalkanes), olefins, alkynes, benzene series, alcohols, aldehydes, ethers, ketones, acids, esters and halogenated hydrocarbons.
[0095] In the present invention, preferably, the manganese-based catalyst is used in the catalytic oxidation reaction of alkanes, more preferably in the catalytic oxidation reaction of propane. In the present invention, the manganese-based catalyst is used for catalytic oxidation of propane, which can maintain a high propane conversion rate at a high volume space velocity.
[0096] In the present invention, the catalytic oxidation reaction device is not particularly limited and can be selected from conventional reaction devices in the art. According to a preferred embodiment of the present invention, the catalytic oxidation reaction is carried out in a fixed bed reaction device.
[0097] In the present invention, the reaction conditions of the catalytic oxidation are not particularly limited, and those skilled in the art can make adaptive adjustments according to the conditions of the catalytic oxidation reaction. Preferably, the reaction conditions include: the reaction pressure is normal pressure, the reaction temperature is 100-600°C, preferably 200-500°C, the volume space velocity is 1000-80000h -1 , preferably 10000-50000h -1 .
[0098] According to a particularly preferred embodiment of the present invention, a method for preparing a manganese-based catalyst by 3D printing comprises the following steps:
[0099] (1) mixing a photosensitive resin mixed liquid with a ceramic powder to obtain a photosensitive ceramic slurry, wherein the mass ratio of the ceramic powder to the photosensitive resin mixed liquid is 1:0.2-1.6, and performing 3D printing to obtain a printed body;
[0100] (2) degreasing and sintering the printed body to obtain a 3D printed ceramic carrier;
[0101] The degreasing process of the printed body comprises: in the first stage, the temperature is raised to 460-530°C at a rate of 3-7°C / min and maintained for 1-3h; in the second stage, the temperature is raised to 680-720°C at a rate of 8-12°C / min and maintained for 2-3h;
[0102] (3) coating the slurry containing manganese oxide on the surface of the 3D printed ceramic carrier, and calcining to obtain a manganese-based catalyst; in step (3), the 3D printed ceramic carrier before coating is subjected to alkali treatment, and the alkali treatment process comprises: immersing the 3D printed ceramic carrier in an alkali solution at 30-80° C. for 1-6 hours; the manganese oxide powder is selected from α-MnO2, Cu x Mn 3-x O4 and Fex Mn 3-x At least one of O4, of which 0 <x<3;
[0103] The total coating amount of the slurry containing manganese oxide on each liter of the 3D printing ceramic support is 50-130 g.
[0104] The present invention will be described in detail below through examples and comparative examples. In the following examples and comparative examples, the room temperature is 25°C;
[0105] The three-dimensional model is established by 3DMAX;
[0106] The 3D printing is completed by a sinking DLP-3D printer (model SU136A) of Foshan Guanglei Intelligent Manufacturing Co., Ltd.
[0107] The planetary ball mill is a JC-QM series vertical planetary ball mill of Juchuang Environmental Protection;
[0108] The vibrating ball mill is a GZM-6 vibrating ball mill produced by Tianjin Shengyuan Equipment Co., Ltd.
[0109] The average particle size of the ceramic powder and the average diameter of the manganese oxide powder in the manganese oxide-containing slurry are equivalent volume diameters obtained by laser particle size method, and the test instrument is Malvern Mastersizer 3000;
[0110] The fixed bed reaction device is a micro fixed bed reaction device designed and manufactured by Tianjin Pengxiang Technology Co., Ltd.
[0111] The test method and test conditions for the specific surface area of the carrier and the coated manganese oxide of the manganese-based catalyst are described in the aforementioned specification and will not be repeated here.
[0112] Example 1
[0113] (1-1) Prepare photosensitive resin mixture:
[0114] Epoxy acrylate prepolymer (Foshan Guanglei Intelligent Manufacturing Co., Ltd.) and 1,6-hexanediol diacrylate (HDDA) were mixed in a mass ratio of 1:1.5, and the mixture was stirred evenly to obtain a photosensitive resin, to which 2,4,6-trimethylbenzoyl-diphenylphosphine oxide and a powder dispersant (Yangzhou Lida Resin Co., Ltd., LD-1241) were added, so that 5 parts of photoinitiator, 92 parts of photosensitive resin, and 3 parts of powder dispersant were contained in every 100 parts by weight of the photosensitive resin mixed liquid, and the photosensitive resin mixed liquid was obtained after stirring evenly;
[0115] (1-2) Preparation of photosensitive ceramic slurry:
[0116] Place the photosensitive resin mixture obtained in (1-1) in a high-speed disperser, weigh cordierite powder (Jushi Mineral Products Processing Plant, Lingshou County, Hebei Province, average particle size 4.5μm), and slowly pour it into the prepared photosensitive resin mixed solution. The mass ratio of ceramic powder to photosensitive resin mixed solution is 1:1. Turn on the high-speed disperser for stirring at a stirring rate of 500rpm. After the ceramic powder is completely poured in, continue stirring for 40 minutes. Use a planetary ball mill to repeatedly grind the obtained preliminarily mixed photosensitive ceramic slurry 4 times, each grinding time is 1h, and the rotation speed is 300rpm to obtain a photosensitive ceramic slurry;
[0117] (1-3) 3D printing:
[0118] The photosensitive ceramic slurry was placed in a material tank, imported into a three-dimensional model, sliced and 3D printed to obtain a printed body with a connected channel structure. The printed body has a vertically staggered structure composed of square cylinders with a side length of 1.2 mm, a cylindrical shape, a bottom diameter of 3 cm, and a height of 1 cm. The 3D printing parameters are as follows: single layer curing thickness 100 μm, single layer illumination time 10 s, illumination intensity 5 mW / cm 2 The printing blank has Figure 1 Similar pore structure.
[0119] (2) Degreasing and sintering of printed body:
[0120] The degreasing process of the printed body includes: in the first stage, the temperature is raised to 500°C at a rate of 5°C / min and maintained for 2h; in the second stage, the temperature is further raised to 700°C at a rate of 10°C / min and maintained for 2h.
[0121] After the degreasing treatment is completed, the temperature is continued to be raised for sintering, and the temperature is continued to be raised to 1400°C at a rate of 10°C / min and maintained for 2 hours; then the temperature is lowered to room temperature at a rate of 5°C / min to obtain a 3D printed ceramic carrier.
[0122] (3-1) Alkali treatment of 3D printed ceramic carrier: The 3D printed ceramic carrier was placed in a 6% KOH aqueous solution with a carrier:alkaline solution mass ratio of 1:9 and treated at 50°C for 6 hours. The carrier after alkali treatment was rinsed with deionized water three times and dried at 110°C for later use.
[0123] (3-2) Preparation and coating of slurry containing manganese oxide:
[0124] The manganese-based spinel structure CuMn2O4 powder was synthesized by NaOH coprecipitation method, dried at 120℃ for 4h, calcined at 450℃ for 3h and cooled to room temperature for use. The CuMn2O4 powder was added to deionized water, the mass ratio of CuMn2O4 powder to deionized water was 1:4, 63% concentrated nitric acid was added to adjust the pH value of the system to less than 4, and the vibrating ball mill was used for grinding. The grinding conditions were: ball milling time 2.5h, speed 1000rpm. The average diameter of the manganese oxide powder in the slurry after ball milling was 10.3μm. The slurry containing manganese oxide was evenly coated on the surface of the 3D printed ceramic carrier.
[0125] (3-3) Post-treatment: The 3D printed ceramic support coated with the slurry containing manganese oxide in (3-2) was dried at 120° C. for 2 h, and the temperature was increased to 400° C. at a rate of 3° C. / min and maintained for 3 h to obtain a manganese-based catalyst. Figure 2 This is a physical photo of the manganese-based catalyst of Example 1.
[0126] Example 2
[0127] (1-1) Prepare photosensitive resin mixture:
[0128] Polyurethane acrylate (Foshan Guanglei Intelligent Manufacturing Co., Ltd.) and trimethylolpropane triacrylate (TMPTA) were mixed in a mass ratio of 1:2, and the mixture was stirred evenly to obtain a photosensitive resin. Isopropyl thioxanthone (ITX) and a powder dispersant (Yangzhou Lida Resin Co., Ltd., LD-1800) were added thereto so that 8 parts of photoinitiator, 88 parts of photosensitive resin, and 4 parts of powder dispersant were contained in every 100 parts by weight of the photosensitive resin mixed liquid. The mixture was stirred evenly to obtain a photosensitive resin mixed liquid.
[0129] (1-2) Preparation of photosensitive ceramic slurry:
[0130] Place the photosensitive resin mixture obtained in (1-1) in a high-speed disperser. Weigh bentonite powder (Jushi Mineral Products Processing Plant, Lingshou County, Hebei Province, average particle size 3.6μm), slowly pour it into the prepared photosensitive resin mixed solution, the mass ratio of ceramic powder and photosensitive resin mixed solution is 1:1.4, turn on the high-speed disperser for stirring, and the stirring rate is 600rpm. After the ceramic powder is completely poured in, continue stirring for 60min. Use a planetary ball mill to repeatedly grind the obtained preliminary mixed photosensitive ceramic slurry 3 times, each grinding time is 1.5h, and the rotation speed is 450rpm to obtain a photosensitive ceramic slurry;
[0131] (1-3) 3D printing:
[0132] The photosensitive ceramic slurry was placed in a material tank, imported into a three-dimensional model, sliced and 3D printed to obtain a printed body with a connected channel structure. The printed body has a vertically staggered structure composed of square cylinders with a side length of 1.8 mm, a cylindrical shape, a bottom diameter of 3 cm, and a height of 1 cm. The 3D printing parameters are as follows: single-layer curing thickness 125 μm, single-layer illumination time 15 s, and illumination intensity 8 mW / cm 2 .
[0133] (2) Degreasing and sintering of printed body:
[0134] The debinding process includes: in the first stage, the temperature is raised to 530°C at a rate of 7°C / min and maintained for 2 hours; in the second stage, the temperature is further raised to 720°C at a rate of 12°C / min and maintained for 2.5 hours. After the debinding treatment is completed, the temperature is further raised to 1500°C at a rate of 10°C / min and maintained for 1.5 hours; then the temperature is lowered to room temperature at a rate of 5°C / min to obtain a 3D printed ceramic carrier.
[0135] (3-1) Alkali treatment of 3D printed ceramic carrier: The 3D printed ceramic carrier was placed in a 18% by mass NaOH aqueous solution, with a carrier:alkaline solution mass ratio of 1:5, and treated at 40°C for 1 h. The carrier after alkali treatment was rinsed with deionized water three times and dried at 100°C for later use.
[0136] (3-2) Preparation and coating of slurry containing manganese oxide:
[0137] Synthesis of manganese-based spinel Co by sodium oxalate coprecipitation 1.5 Mn 1.5 O4 powder was dried at 120℃ for 4h, calcined at 450℃ for 3h and then cooled to room temperature for use. 1.5 Mn 1.5 O4 powder was added into deionized water, Co 1.5 Mn 1.5 The mass ratio of O4 powder to deionized water was 1:3, 63% concentrated nitric acid was added to adjust the pH value of the system to less than 4, and a vibrating ball mill was used for full grinding. The grinding conditions were: ball milling time 2h, speed 1100rpm. The average diameter of the manganese oxide powder in the slurry after ball milling was 12μm. The slurry containing manganese oxide was evenly coated on the surface of the 3D printing ceramic carrier.
[0138] (3-3) Post-treatment: The 3D printed ceramic support coated with the manganese oxide-containing slurry in (3-2) was dried at 120°C for 2 h, heated to 450°C at a rate of 3°C / min, and maintained for 3 h to obtain a manganese-based catalyst.
[0139] Example 3
[0140] (1-1) Prepare photosensitive resin mixture:
[0141] Polyurethane acrylate (Foshan Guanglei Intelligent Manufacturing Co., Ltd.) and tripropylene glycol diacrylate (TPGDA) were mixed in a mass ratio of 1:0.8, and the mixture was stirred evenly to obtain a photosensitive resin, to which phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide (photoinitiator 819) and a powder dispersant (Yangzhou Lida Resin Co., Ltd., LD-1800) were added, so that 3 parts of photoinitiator, 92 parts of photosensitive resin, and 5 parts of powder dispersant were contained in every 100 parts by weight of the photosensitive resin mixed liquid, and the photosensitive resin mixed liquid was stirred evenly to obtain a photosensitive resin mixed liquid;
[0142] (1-2) Preparation of photosensitive ceramic slurry:
[0143] Place the photosensitive resin mixture obtained in (1-1) in a high-speed disperser, weigh kaolin powder (Jushi Mineral Products Processing Plant, Lingshou County, Hebei Province, average particle size 2.8μm), and slowly pour it into the prepared photosensitive resin mixed solution. The mass ratio of ceramic powder to photosensitive resin mixture is 1:0.5. Turn on the high-speed disperser for stirring at a stirring rate of 400rpm. After the ceramic powder is completely poured in, continue stirring for 25min. Grind the preliminarily mixed photosensitive ceramic slurry repeatedly 5 times using a planetary ball mill, each grinding time is 0.8h, and the rotation speed is 450rpm to obtain a photosensitive ceramic slurry;
[0144] (1-3) 3D printing:
[0145] The photosensitive ceramic slurry was placed in a material tank, imported into a three-dimensional model, sliced and 3D printed to obtain a printed body with a connected channel structure. The printed body has a vertically staggered structure composed of square cylinders with a side length of 0.8 mm, a cylindrical shape, a bottom diameter of 3 cm, and a height of 1 cm. The 3D printing parameters are as follows: single-layer curing thickness 40 μm, single-layer illumination time 15 s, and illumination intensity 3 mW / cm 2 .
[0146] (2) Degreasing and sintering of printed body:
[0147] The debinding process includes: the first stage is to heat up to 460℃ at a rate of 3℃ / min and keep it for 2h; the second stage is to heat up to 680℃ at a rate of 8℃ / min and keep it for 3h. After the debinding treatment is completed, the temperature is continued to be raised to 1350℃ at a rate of 10℃ / min for sintering, and then it is cooled to room temperature at a rate of 5℃ / min;
[0148] (3-1) Alkali treatment of 3D printed ceramic carrier: The 3D printed ceramic carrier was placed in a 10% by mass KOH aqueous solution, with a carrier:alkaline solution mass ratio of 1:6, and treated at 80°C for 2 h. The carrier after alkali treatment was rinsed with deionized water three times and dried at 90°C for later use.
[0149] (3-2) Preparation and coating of slurry containing manganese oxide:
[0150] The single manganese oxide α-MnO2 powder was synthesized by hydrothermal method, dried at 120℃ for 4h, calcined at 450℃ for 3h and cooled to room temperature for use. The α-MnO2 powder was added to deionized water, and the mass ratio of α-MnO2 powder to deionized water was 1:6. Then 63% concentrated nitric acid was added to adjust the system to a pH value of less than 4. A vibrating ball mill was used for full grinding. The grinding conditions were: ball milling time 3h, speed 800rpm. The average diameter of the manganese oxide powder in the slurry after ball milling was 8μm. The slurry containing manganese oxide was evenly coated on the surface of the 3D printed ceramic carrier.
[0151] (3-3) Post-treatment: The 3D printed ceramic support coated with the manganese oxide-containing slurry in (3-2) was dried at 120°C for 2 h, and then heated to 450°C at a rate of 3°C / min and maintained for 3 h to obtain a manganese-based catalyst.
[0152] Example 4
[0153] The catalyst was prepared according to the method of Example 1, except that no alkali treatment was performed before coating the slurry containing manganese oxide in step (3). Other conditions were the same as those of Example 1.
[0154] Example 5
[0155] The catalyst was prepared according to the method of Example 1, except that the degreasing in step (2) was carried out under the following conditions: the temperature was increased to 850° C. at a rate of 15° C. / min and maintained for 5 h.
[0156] Example 6
[0157] The catalyst was prepared according to the method of Example 1, except that the amount of manganese oxide powder added was changed so that the total coating amount of the prepared catalyst on each liter of ceramic carrier was 30 g / L.
[0158] Comparative Example 1
[0159] (1) A customized commercial cordierite carrier (Jiangxi Guoci Environmental Protection Technology Co., Ltd., ceramic honeycomb carrier) was used, with a bulk density of 0.5 kg / L, a pore volume of 0.5 mL / g, and a single cubic column straight channel inside; it was cut into a cylinder with the same size as Example 1 as a carrier (bottom diameter 3 cm, height 1 cm);
[0160] (2) The cordierite carrier obtained in step (1) is subjected to alkali treatment, coating with a slurry containing manganese oxide, and post-treatment, under the same conditions as in Example 1.
[0161] Comparative Example 2
[0162] (1) A customized commercial cordierite carrier (Jiangxi Guoci Environmental Protection Technology Co., Ltd., ceramic honeycomb carrier) was used, with a bulk density of 0.5 kg / L, a pore volume of 0.5 mL / g, and a single cubic column straight channel inside; it was cut into a cylinder with the same size as Example 1 as a carrier (bottom diameter 3 cm, height 1 cm);
[0163] (2) The cordierite carrier obtained in step (1) is subjected to alkali treatment, and an active component slurry containing Pt and Al2O3 is coated on the surface of the carrier after alkali treatment. An appropriate amount of Al2O3 and H2PtCl6 is added to deionized water, and the mixture is fully ground using a vibrating ball mill (Tianjin Shengyuan Equipment Co., Ltd., GZM-6). The specific grinding conditions are: ball milling time 2.5h, rotation speed 1000rpm, and the average particle diameter of the mixed solution after grinding is 10μm; the mixed solution after grinding is stirred for 1 hour to obtain an active component slurry, and the solid content of the slurry is controlled to be 15wt%, and then the active component slurry is evenly coated on the surface of the carrier, so that the total coating amount of the coating is 60g / L, of which the coating amount of Pt is 0.25g / L, and the rest is the Al2O3 active component. After the coating is completed, it is dried and roasted, and the drying and roasting conditions are the same as those in Example 1.
[0164] Comparative Example 3
[0165] The catalyst was prepared according to the method of Example 1, except that no manganese oxide coating was performed and step (3-2) was not performed.
[0166] Comparative Example 4
[0167] The catalyst was prepared according to the method of Example 1, except that in step (3), an active component slurry containing Pt and Al2O3 was coated on the carrier. Appropriate amounts of Al2O3 and H2PtCl6 were added to deionized water, and the mixture was fully ground using a vibrating ball mill (Tianjin Shengyuan Equipment Co., Ltd., GZM-6). The specific grinding conditions were: ball milling time of 2.5 hours, rotation speed of 1000 rpm, and average particle diameter of the mixed solution after grinding was 10 μm; the mixed solution after grinding was stirred for 1 hour to obtain an active component slurry, and the solid content of the slurry was controlled to be 15wt%, and then the active component slurry was uniformly coated on the surface of the carrier, so that the total coating amount of the coating was 60g / L, of which the coating amount of Pt was 0.25g / L, and the rest was the Al2O3 active component. After the coating was completed, it was dried and calcined, and the drying and calcining conditions were the same as those in Example 1.
[0168] Test Example 1
[0169] The specific surface areas of the carriers and the specific surface areas of the coated manganese oxides of the manganese-based catalysts prepared in the examples and comparative examples are shown in Table 1.
[0170] Table 1
[0171]
[0172] It can be seen from the results in Table 1 that the catalyst carrier of the alkali-treated embodiment of the present invention has a larger specific surface area than the traditional cordierite honeycomb carrier, which is beneficial to the full dispersion of the manganese oxide active component and the catalytic oxidation reaction of VOCs.
[0173] Example 4 The catalyst was prepared according to the method of Example 1, except that no alkali treatment was performed in step (3). The specific surface area of the carrier was smaller than that of Example 1, and the active component loading was also smaller than that of Example 1.
[0174] Test Example 2
[0175] The catalytic activity of the catalysts in the examples and comparative examples was evaluated by the activity of the catalytic oxidation reaction of propane. The reaction was carried out in a micro fixed bed reactor designed and manufactured by Tianjin Pengxiang Technology Co., Ltd., equipped with a Multigas 2030 infrared detector from MKS.
[0176] The catalytic oxidation reaction conditions are as follows: the reaction is carried out under normal pressure, the initial temperature is 250°C, the temperature is increased to 480°C at a rate of 5°C / min, the inlet gas volume composition is 600ppmv propane + 21% O2 + 79% N2, and the volume space velocity is 26000h -1 The propane conversion rate at 400°C is shown in Table 2.
[0177] Propane conversion rate = 1 - (residual propane content / propane raw material content) x 100%.
[0178] Table 2
[0179] serial number Propane conversion rate (%) Example 1 87.6 Example 2 78.1 Example 3 84.4 Example 4 79.3 Example 5 82.3 Example 6 77.6 Comparative Example 1 66.5 Comparative Example 2 39.7 Comparative Example 3 1.2 Comparative Example 4 49.7
[0180] It can be seen from the results in Table 2 that the catalysts prepared by the methods of Examples 1-6 of the present invention have higher propane oxidation activity when performing the catalytic oxidation reaction of propane, and the propane conversion rate can reach more than 77%. Figure 3 The relationship between the conversion rate and temperature of propane catalytic oxidation of Examples 1-6 and Comparative Examples 1-4 is shown in FIG. Figure 3 It can be seen that at the same reaction temperature, the propane conversion rate of the catalyst prepared in the example is higher than that of the catalyst prepared in the comparative example. Compared with Example 1, Example 4 was not subjected to alkali treatment, the specific surface area of the carrier was too small, the active component loading was small, and the propane conversion rate was lower under the same conditions.
[0181] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A method for preparing a manganese-based catalyst by 3D printing, characterized in that: The following steps are involved: (1) mixing a photosensitive resin mixed liquid with a ceramic powder to obtain a photosensitive ceramic slurry, and performing 3D printing to obtain a printed body; (2) degreasing and sintering the printed body to obtain a 3D printed ceramic carrier; (3) Coating a slurry containing manganese oxide on the surface of a 3D printed ceramic carrier and calcining the slurry to obtain a manganese-based catalyst.
2. The method according to claim 1, wherein: Based on 100 parts by mass of the photosensitive resin mixed liquid, it includes 0.5-10 parts of photoinitiator, 85-95 parts of photosensitive resin, and 2-10 parts of powder dispersant, preferably including 3-8 parts of photoinitiator, 88-92 parts of photosensitive resin, and 3-5 parts of powder dispersant; Preferably, the photoinitiator is selected from at least one of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide and isopropylthioxanthone; Preferably, the photosensitive resin is a mixture of an acrylate prepolymer and an acrylate monomer, and the acrylate prepolymer is an epoxy acrylate prepolymer and / or a polyurethane acrylate prepolymer; Preferably, the mass ratio of the acrylate prepolymer to the acrylate monomer in the photosensitive resin is 1:0.6-2.2, preferably 1:0.8-2.
3. The method according to claim 1 or 2, wherein: In step (1), the mass ratio of the ceramic powder to the photosensitive resin mixture is 1:0.1-2, preferably 1:0.2-1.6; Preferably, the ceramic powder is a natural aluminosilicate mineral clay, preferably at least one selected from cordierite, kaolin and bentonite; Preferably, the average particle size of the ceramic powder is less than 10 μm, preferably 2.5-5 μm.
4. The method according to any one of claims 1 to 3, wherein: The 3D printing conditions include: single layer curing thickness 20-150 μm, single layer illumination time 5-20 s, illumination intensity 2-10 mW / cm 2 ; Preferably, the printed body has a vertically staggered structure consisting of cubic columns with a bottom side length of 0.5-2 mm.
5. The method according to any one of claims 1 to 4, wherein: In step (2), the process of degreasing the printed body includes: heating at a temperature of 400-800° C. and a heating time of 1-10 h; Preferably, the degreasing of the printed body is divided into two stages: in the first stage, the temperature is increased to 450-550°C at a rate of 3-8°C / min and maintained for 0.5-4h, preferably increased to 460-530°C at a rate of 3-7°C / min and maintained for 1-3h; In the second stage, the temperature is further increased to 650-750°C at a rate of 8-15°C / min and maintained for 1-3h, preferably increased to 680-720°C at a rate of 8-12°C / min and maintained for 2-3h; Preferably, the sintering conditions include: sintering temperature of 1300-1600°C, preferably 1350-1500°C; sintering time of 1-3h, preferably 1.5-2.5h; heating rate of 8-15°C / min, preferably 9-12°C / min; Preferably, after sintering, the temperature is cooled to room temperature at a cooling rate of 3-8°C / min, preferably 4-6°C / min.
6. The method according to any one of claims 1 to 5, wherein: Step (3) further includes subjecting the 3D printed ceramic carrier before coating to an alkali treatment, wherein the alkali treatment process includes: immersing the 3D printed ceramic carrier in an alkali solution at 30-80° C. for 0.5-10 hours, preferably 1-6 hours; Preferably, the alkali solution is a NaOH and / or KOH aqueous solution, and the mass fraction of NaOH and / or KOH is 4%-20%, preferably 6-18%; Preferably, the mass ratio of the 3D printing ceramic carrier to the alkali solution is 1:4-10, preferably 1:5-9; Preferably, the specific surface area of the 3D printing ceramic carrier after alkali treatment is 6-20m 2 / g, preferably 8-15m 2 / g.
7. The method according to any one of claims 1 to 6, wherein: In step (3), the total coating amount of the slurry containing manganese oxide per liter of the 3D printing ceramic carrier is 40-160 g, preferably 50-130 g; Preferably, the manganese oxide-containing slurry comprises manganese oxide powder and deionized water; Preferably, the mass ratio of the manganese oxide powder to deionized water is 1:2.5-9, preferably 1:3-6; Preferably, the manganese oxide powder is selected from at least one of single manganese oxide, manganese-based spinel, manganese-based perovskite and manganese-based mullite; Preferably, the average diameter of the manganese oxide powder in the manganese oxide-containing slurry is less than 15 μm, preferably 7-13 μm.
8. The method according to claim 7, wherein: The single manganese oxide is selected from at least one of α-MnO2, β-MnO2, γ-MnO2, δ-MnO2, λ-MnO2, ε-MnO2, α-Mn2O3 and Mn3O4; Preferably, the manganese-based spinel comprises A x Mn 3-x O4, A is at least one selected from Mg, Ca, Fe, Co, Ni, Cu and Zn, 0 <x<3; Preferably, the manganese-based perovskite comprises BMnO3, and B is selected from at least one of La, Sm, Sr and Ca; Preferably, the manganese-based mullite comprises CMn2O5, and C is selected from at least one of Y, La and Sm.
9. The method according to any one of claims 1 to 8, wherein: In step (3), the calcination temperature is 300-650°C, preferably 400-450°C, and the calcination time is 1-5h, preferably 2-4h; Preferably, when the manganese oxide powder contains at least one of α-MnO2, β-MnO2, γ-MnO2, δ-MnO2, λ-MnO2, ε-MnO2 and manganese-based spinel, the calcination process comprises: heating to 300-450°C at a rate of 3-6°C / min and maintaining for 2-4h; Preferably, when the manganese oxide powder does not contain at least one of α-MnO2, β-MnO2, γ-MnO2, δ-MnO2, λ-MnO2, ε-MnO2 and manganese-based spinel, the calcination process includes: heating to 350-650°C at a rate of 3-6°C / min and maintaining for 2-4h.
10. A manganese-based catalyst prepared by the method according to any one of claims 1 to 9; Preferably, the manganese-based catalyst comprises a carrier and a manganese oxide coated on the surface of the carrier; Preferably, the specific surface area of the carrier of the manganese-based catalyst is 6-20 m 2 / g, preferably 8-15m 2 / g; Preferably, the specific surface area of the manganese oxide coated on the surface of the manganese-based catalyst is 10-80 m 2 / g, preferably 20-60m 2 / g.
11. Use of the manganese-based catalyst according to claim 10 in catalytic oxidation reactions.
Citation Information
Patent Citations
Catalysts for treating benzene compounds in industrial waste gas and their preparation methods
CN106890642B
Honeycomb ceramic type monolithic catalyst using mayenite as coating layer, preparation method and application thereof
CN101637725A
Method for preparing structured catalyst carrier through photocuring
CN111760596A
Spherical denitration catalyst with lattice structure prepared by 3D printing and preparation method thereof
CN112536026A
Kaolin-based 3D printing powder and integral active porous material prepared from kaolin-based 3D printing powder
CN115304392A
Cited By
Precious metal catalyst based on additive manufacturing and preparation method thereof
CN122098549A
A noble metal catalyst based on additive manufacturing and its preparation method
CN122098549B